2015
DOI: 10.1007/s00464-015-4450-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sleeve gastrectomy with 27 versus 39 Fr bougie calibration: a randomized controlled trial

Abstract: The use of different bougie diameters had no impact on the volume of resected stomach, morbidity or short-term weight loss after LSG, although a trend was seen toward better weight loss with the smaller bougie. A longer-lasting follow-up will be necessary to further assess differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…Eight studies (2168 patients; 4 treatment nodes) were found to investigate EWL with different bougie sizes after LSG in the current NMA (the network structure figure is shown in Fig. 2 A) 14 , 18 21 , 23 , 24 , 26 . Figure 3 A presents results of EWL percentage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies (2168 patients; 4 treatment nodes) were found to investigate EWL with different bougie sizes after LSG in the current NMA (the network structure figure is shown in Fig. 2 A) 14 , 18 21 , 23 , 24 , 26 . Figure 3 A presents results of EWL percentage.…”
Section: Resultsmentioning
confidence: 99%
“…Although several systemic meta-analyzes, based on pooled data from case series and randomized controlled trials (RCTs), have been published, the standard bougie size for LSG is not yet established 16 , 17 , 21 , 23 – 28 . Herein, we performed a network meta-analysis and cataloged results of these controlled trials into a comprehensive systematic review and meta-analysis of available data to determine the standard bougie size for calibration during LSG, based on excess weight loss (EWL), associated complications, and SLL percentage.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Parikh et al ( 15 ) compared 40-Fr and 50-Fr bougies and reported no differences in weight loss. Cal et al ( 16 ) conducted the only randomized controlled trial that investigated the relationship between weight loss and bougie diameter in 126 patients who underwent LSG; the results showed that the use of different bougie diameters had no effect on EWL after LSG. Despite the contradicting findings in the literature, surgeons have increasingly used narrow bougies to decrease the risk of weight regain.…”
Section: Discussionmentioning
confidence: 99%
“…21,28 Current substance use is seen in less than 2% of candidates for bariatric surgery; an active disorder is a contraindication to bariatric surgery. 7,29 There is a strong relationship between obesity and quality of life. [30][31][32] Individuals often report significant difficulties with physical (walking, climbing stairs) and occupational functioning.…”
Section: Psychosocial Status Of Candidates For Bariatric Surgerymentioning
confidence: 99%